Mechanical Behavior of PET-G Tooth Aligners Under Cyclic Loading - Cianci, Claudia; Pappalettera, Giovanni; Renna, Gilda; Casavola, Caterina; Laurenziello, Michele; Battista, Giovanni; Pappalettere, Carmine; Ciavarella, Domenico (Frontiers in Materials, 2020)
Invisible aligners are medical devices, which allow repositioning of teeth through a treatment designed by the orthodontists. During this orthodontic treatment, patients use several aligners each for a couple of weeks. The aligner will apply a system of forces on the teeth to shift them into desired position. Since aligners exert forces thanks to their particular shape, it is important that during lifetime's service they do not undergo significant deformations. This research aims to study the mechanical behavior of invisible aligners made by polyethylene terephthalate-glycol (PET-G), which is one of most used the plastic materials to produce these devices. In this study, cyclic compression tests in atmospheric environment (~25°C) as well as in the presence of saliva (to simulate intraoral environment) were performed. The mechanical behavior of two different thicknesses aligners (0.75 and 0.88 mm) was studied. In particular, each aligner was subjected to 22500 load cycles from 0 to 50 N. The number of load cycles simulates the average load history to which an aligner is subjected during its lifetime. The tests were performed on a testing machine, using a hard resin dental casts appropriately fixed to the machine. Analysis of the results shows that stiffness of aligners material increases during the cyclic test. In particular, it was observed a gradual reduction of crosshead displacement during the test, highlighting the occurrence of cyclic hardening phenomena. It was also found that the aligners show a residual strain recovery after removing the applied load. Moreover, in the analyzed load range rate, the aligners show a low tendency to accumulate residual strains as loading cycles progress.